DNA methylome: Unveiling your biological age - Li, Ming (Protein Cell, 2013)
Hannum and colleagues performed DNA methylation sequencing to examine the relationship between DNA methylome and aging rate. Notably, they succeeded in building a quantitative and reproducible model based on the epigenetic bio-markers to predict aging rate with high accuracy. This progress enlightens us in many aspects particularly in applying this novel set of bio-markers on studying the mechanism of aging rate using adult tissue-specific stem cells, building up a potential quantitative model to explore the mechanism for other epigenetic factors like non-coding RNA, and understanding the principle and mechanism of 3D chromatin structure in epigenetic modulation.